2008
DOI: 10.1055/s-2008-1059304
|View full text |Cite
|
Sign up to set email alerts
|

Einfluß von Alkohol auf die Hämodynamik der Pfortader bei nutritiv-toxischer Leberzirrhose

Abstract: The influence of alcohol on portal vein haemodynamics was assessed prospectively in 30 patients (20 men, 10 women; mean age 54.3 [34-70] years) with nutritional-toxic cirrhosis of the liver (Child-Pugh stages A-C) and portal vein hypertension. During the period of observation hepatic vein occlusion pressure as an indirect measure of portal vein pressure was repeatedly determined. In addition, the size of oesophageal varices and the Child-Pugh stage were monitored. After complete alcohol abstinence of one year,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…The mechanisms underlying the consequences of alcohol consumption on liver-related outcomes are possibly related to the worsening of portal hemodynamics. Alcohol use can deteriorate portal hypertension in patients with cirrhosis not only due to structural changes but also by modulating its dynamic component [32] leading to acute and chronic increases in intrahepatic vascular resistance [33,34]. Long-term abstinence has been linked to significant decreases of up to 40% in portal pressure which leads to regression of varices and reduced occurrence of portal hypertension-related complications [28].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the consequences of alcohol consumption on liver-related outcomes are possibly related to the worsening of portal hemodynamics. Alcohol use can deteriorate portal hypertension in patients with cirrhosis not only due to structural changes but also by modulating its dynamic component [32] leading to acute and chronic increases in intrahepatic vascular resistance [33,34]. Long-term abstinence has been linked to significant decreases of up to 40% in portal pressure which leads to regression of varices and reduced occurrence of portal hypertension-related complications [28].…”
Section: Discussionmentioning
confidence: 99%
“…The interruption of etiology is the most important step, mainly with respect to the progression of liver disease but also with respect to an immediate portal pressure-lowering effect. This holds true for the interruption of hepatitis C 91 93 or abstinence from alcohol 94 . Since chronic alcoholism is now the most frequent cause of liver cirrhosis and portal hypertension in most countries, we need a more holistic approach to alcohol use disorders 95 , 96 .…”
Section: Modification Of Portal Pressure By Non-specific Drugsmentioning
confidence: 94%
“…Thus, it is eminently worthwhile to support beneficial change in the eating or drinking habits of patients, which are controlled by the brain. It has been shown that in patients with liver cirrhosis, weight loss 200 or abstinence from alcohol 94 , 201 significantly reduces portal hypertension. This appears to be the most important strategy to influence the gut–liver axis and portal hypertension ( Figure 1 ).…”
Section: Modulation Of the Intestinementioning
confidence: 99%
“…Об этом свидетельствуют наблюдения за больными алкогольным ЦП, описанные еще в начале 90-х гг. прошлого столетия, у которых длительное воздержание от приема алкоголя способствовало регрессии варикознорасширенных вен пищевода [56] и сопровождалось снижением заклиненного печеночного венозного давления на 46% [57].…”
Section: текущие подходы к лечению алкоголь-индуцированного фиброза п...unclassified